Fixed Rate Loan Commitments, Take-Down Risk, and the Dynamics of Hedging with Futures - Ho, Thomas S. Y.; Saunders, Anthony (Journal of Financial and Quantitative Analysis, 1983)
Thomas S. Y. Ho, Anthony Saunders, Fixed Rate Loan Commitments, Take-Down Risk, and the Dynamics of Hedging with Futures, The Journal of Financial and Quantitative Analysis, Vol. 18, No. 4 (Dec., 1983), pp. 499-516